2019
DOI: 10.3390/ijms20215261
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of GPR68 Expression in Normal and Neoplastic Human Tissues Using a Novel Rabbit Monoclonal Antibody

Abstract: GPR68 (OGR1) belongs to the proton-sensing G protein-coupled receptors that are involved in cellular adaptations to pH changes during tumour development. Although expression of GPR68 has been described in many tumour cell lines, little is known about its presence in human tumour entities. We characterised the novel rabbit monoclonal anti-human GPR68 antibody 16H23L16 using various cell lines and tissue specimens. The antibody was then applied to a large series of formalin-fixed, paraffin-embedded normal and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
(61 reference statements)
3
11
0
Order By: Relevance
“…In the pancreas, OGR1-positive cells (Figure S3) revealed a similar staining pattern to those shown by Herzig [50]. This group elegantly demonstrated that the OGR1-positive cells in the pancreas are glucagon-producing islet cells [50]. In our current study, immunostaining of duodenum tunica muscularis revealed OGR1-positive staining in macrophages, granulocytes, endothelial cells, and fibroblasts (Figure 2D).…”
Section: Ogr1 Immunohistochemistry Shows Ogr1 Expression In Healthy I...supporting
confidence: 85%
See 2 more Smart Citations
“…In the pancreas, OGR1-positive cells (Figure S3) revealed a similar staining pattern to those shown by Herzig [50]. This group elegantly demonstrated that the OGR1-positive cells in the pancreas are glucagon-producing islet cells [50]. In our current study, immunostaining of duodenum tunica muscularis revealed OGR1-positive staining in macrophages, granulocytes, endothelial cells, and fibroblasts (Figure 2D).…”
Section: Ogr1 Immunohistochemistry Shows Ogr1 Expression In Healthy I...supporting
confidence: 85%
“…In the mucosal duodenum, OGR1-positive cells included macrophages, granulocytes, and endothelial cells (Figure 2C). In the pancreas, OGR1-positive cells (Figure S3) revealed a similar staining pattern to those shown by Herzig [50]. This group elegantly demonstrated that the OGR1-positive cells in the pancreas are glucagon-producing islet cells [50].…”
Section: Ogr1 Immunohistochemistry Shows Ogr1 Expression In Healthy I...supporting
confidence: 65%
See 1 more Smart Citation
“…Other studies showed GPR68 overexpression in human medulloblastoma tissue [172] and in head and neck squamous cancer [173]. Finally, immunohistochemical analysis detected significant GPR68 expression in endocrine or neuroendocrine tumors with origin in the pituitary, the thyroid gland, or the respiratory and digestive systems [174]. More detailed analysis on the expression of GPR68 in particular tumor cell types, showed a significant expression in cancer epithelial cells and fibroblasts of pancreatic ductal adenocarcinomas [171] and in hematopoietic and mesenchymal cells of colorectal tumors [175].…”
Section: G-protein-coupled Receptor 65 (Gpr65)mentioning
confidence: 85%
“…Such GPCRomics approaches [48] have highlighted potential therapeutic targets, such as GPR68 [47,49]. Research tools will be invaluable to further validate these potential targets for therapeutic relevance [50]. Therapeutic areas in which GPCRs have been identified as suitable targets for antibodybased molecules are shown.…”
Section: Targeting Opportunities In the Therapeutic Gpcr-antibody Lanmentioning
confidence: 99%